2007
DOI: 10.1098/rstb.2006.2017
|View full text |Cite
|
Sign up to set email alerts
|

Brain tumour stem cells: the undercurrents of human brain cancer and their relationship to neural stem cells

Abstract: Conceptual and technical advances in neural stem cell biology are being applied to the study of human brain tumours. These studies suggest that human brain tumours are organized as a hierarchy and are maintained by a small number of tumour cells that have stem cell properties. Most of the bulk population of human brain tumours comprise cells that have lost the ability to initiate and maintain tumour growth. Although the cell of origin for human brain tumours is uncertain, recent evidence points towards the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 165 publications
0
51
0
Order By: Relevance
“…A ccording to the cancer stem cell (CSC) hypothesis, tumors are formed and maintained by a population of undifferentiated cells that are characterized by their ability for self-renewal and to induce tumorigenesis (1,2). Critical to CSC research is their prospective identification and isolation from tumor tissue.…”
mentioning
confidence: 99%
“…A ccording to the cancer stem cell (CSC) hypothesis, tumors are formed and maintained by a population of undifferentiated cells that are characterized by their ability for self-renewal and to induce tumorigenesis (1,2). Critical to CSC research is their prospective identification and isolation from tumor tissue.…”
mentioning
confidence: 99%
“…Studies of these cells have revealed that they share certain features with neural stem cells (NSCs), leading to the enticing hypothesis that tumour-initiating cells in the brain arise from the oncogenic transformation of endogenous NSCs, or from dedifferentiated committed neural progenitors or mature glial cells (Dirks, 2008). If such BTSCs can be identified, they can be specifically targeted in the treatment of brain tumours, an exciting possibility with obvious clinical impact.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tumour cells with stem-like properties, called brain tumour stem cells (BTSCs), have been isolated from various adult and pediatric brain tumours, leading to the suggestion that cancer growth might be fuelled by a small population of such cells (Dirks, 2008). Studies of these cells have revealed that they share certain features with neural stem cells (NSCs), leading to the enticing hypothesis that tumour-initiating cells in the brain arise from the oncogenic transformation of endogenous NSCs, or from dedifferentiated committed neural progenitors or mature glial cells (Dirks, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…5 The other factors that contribute to resistance in GBM include (a) high degree of heterogeneity of the tumor and (b) the microenvironment comprising of tumor-associated parenchymal cells such as vascular cells, microglia, and peripheral immune cells, and (c) cancer stem cells (CSC) that actively promote tumor progression. 6 The CSC or glioma initiating cells/glioma stem cells (GIC/GSC) constitute a small population of a tumor, retain stem-like cell features including self-renewal capacity that is crucial for tumorigenicity, 7,8 and confer resistance to radiotherapy and chemotherapy, which leads to recurrence and cancer relapse. [9][10][11] Therefore, GSCs represent a promising target for anti-GBM therapies.…”
Section: Introductionmentioning
confidence: 99%